Resilient Greenway: A Participatory Planning Framework - Chingwen Cheng; Mohsen Garshasby (Fábos Conference on Landscape and Greenway Planning, 2016)
Greenway as a network of “nature’s super infrastructure”—as part of green infrastructure that includes both man-made and natural ecological networks— providing ecological, recreational, and cultural values (Fabos, 1995) is a complex and dynamic social-ecological system. The structures and functions of greenways are shaped and formed by the interactions between natural and human systems. Under climate change impacts with intensified and more frequent extreme weathers, many greenway systems that are particularly in already natural disaster-prone areas would be likely to experience more aggravated social and ecological impacts. A resilient greenway thus is a greenway system that processes an adaptive capacity to absorb shocks and cope with disturbance to the system while maintaining the essential functioning of the system, and a transformative capacity to allow the system to learn and evolve toward sustainability. Greenway systems pertaining ecosystem services have been identified as a critical instrument for climate change mitigation (e.g., carbon sequestration) and adaptation (e.g., reduce heat and floods, improve air and water quality) (Demuzere et al., 2014). Planning for resilient greenway system under climate change impacts is therefore both a remedy for and a challenge with climate change. The capacity of greenway system for climate change is influenced not only by the biophysical characteristics but also social-cultural and institutional context of the system (Matthews and Byrne, 2015). Ahern (2013) identified ecological principles for biophysical resilience of urban landscapes— biodiversity, ecological connectivity, multifunctionality, modularity, and safeto- fail design—while others included participatory consensus-based decisionmaking process and the understanding of community’s perceptions and behaviours toward greenways as social-institutional components to the success of the greenway planning and design (e.g., Benedict and McMahon, 2006; Ryan and Walker, 2005). This paper draws literature from resilience and participatory action research and proposes a resilient greenway participatory planning framework that is place-based and action-oriented to address both biophysical and socialinstitutional resilience of the greenway systems and apply to an on-going study in Kearny, Arizona, USA.
Keywords: greenways; resilient; participatory planning; ecosystem services